Plasmodium falciparum gametocyte carriage, sex ratios and asexual parasite rates in Nigerian children before and after a treatment protocol policy change instituting the use of artemisinin-based combination therapies - Grace Olusola Gbotosho; Akintunde Sowunmi; Christian Tientcha Happi; Titilope Modupe Okuboyejo (Memorias do Instituto Oswaldo Cruz, 2011)
The effects of artemisinin-based combination therapies (ACTs) on transmission of Plasmodium falciparum were evaluated after a policy change instituting the use of ACTs in an endemic area. P. falciparum gametocyte carriage, sex ratios and inbreeding rates were examined in 2,585 children at presentation with acute falciparum malaria during a 10-year period from 2001-2010. Asexual parasite rates were also evaluated from 2003-2010 in 10,615 children before and after the policy change. Gametocyte carriage declined significantly from 12.4% in 2001 to 3.6% in 2010 (@@χ2 for trend = 44.3, p < 0.0001), but sex ratios and inbreeding rates remained unchanged. Additionally, overall parasite rates remained unchanged before and after the policy change (47.2% vs. 45.4%), but these rates declined significantly from 2003-2010 (@@χ2 for trend 35.4, p < 0.0001). Chloroquine (CQ) and artemether-lumefantrine (AL) were used as prototype drugs before and after the policy change, respectively. AL significantly shortened the duration of male gametocyte carriage in individual patients after treatment began compared with CQ (log rank statistic = 7.92, p = 0.005). ACTs reduced the rate of gametocyte carriage in children with acute falciparum infections at presentation and shortened the duration of male gametocyte carriage after treatment. However, parasite population sex ratios, inbreeding rates and overall parasite rate were unaffected.